Internalization of green social work values in the Climate Village Program in Ujungalang Village Cilacap Regency - Ramdani, Jaka (Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The impact of climate change has been a concern for the world, including Indonesia. The government launched a national-scale Climate Village Program in response to such conditions. Researchers explored this program through a study on the internalization of the values of Green Social Work in the Climate Village Program in Ujungalang Village, Cilacap Regency, Central Java Province. The method applied in the exploration was a qualitative method employing a case study approach. The case study was carried out considering that the case in Ujungalang Village was unique. The results showed that the Climate Village Program in Ujungalang Village had internalized the Green Social Work value system, including equality, social inclusion, equitable distribution of resources, and rights-based. The value system developed dynamically to realize sustainable community welfare. In addition, the Climate Village Program also applies the concept of community empowerment (community-based development). These activities are carried out by the community and their institutions, which aim to mobilize and manage human and natural resources within and outside the village and to direct and strengthen adaptation and mitigation efforts to the impacts of climate change.